The Influence of Perception of Convenience, Benefits, and Risks on the Decision to Use DANA E-Wallet Among Generation Z in East Jakarta City - Chika Nurfadillah; Sri Indah Nikensari; Dicky Iranto (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: The main objective of this study is to examine the influence of perceived ease of use, perceived benefits, and perceived risks on the decision to use the DANA E-Wallet among Generation Z in East Jakarta. Methodology: The methodology used is a quantitative approach. This study was conducted only in East Jakarta with 102 Generation Z respondents residing in East Jakarta. The data analysis techniques employed in this study include instrument testing, prerequisite analysis testing, hypothesis testing using partial tests (t-test), and multiple linear regression analysis. Main Findings: The results of the testing conducted in this study show that perceived ease of use, perceived benefits, and perceived risks have a positive and significant impact on the decision to use the DANA e-wallet among Generation Z in East Jakarta. Novelty/Originality of this study: The COVID-19 pandemic has accelerated the adoption of technology, including the use of e-wallets. Studies conducted after the pandemic may show changes in consumer behavior, particularly in the digital financial transaction habits of Generation Z. Research focusing on the behavior of Generation Z in major cities in Indonesia, such as East Jakarta, could provide novelty, considering the unique cultural and economic context of the region.